THU0229 Absolute reduction of peripheral cd4+cd25+foxp3+t regulatory cells in patients with spondyloarthropathy-related oculopathy. (12th June 2018) - Liu, X.; Chai, G.; Duan, Y.; Gao, C.; Li, X.
Abstract : Background: Spondyloarthropathy is a group of systemic chronic autoimmune diseases, which is characterised by the spine, peripheral joint, joint tissue inflammation and high morbidity. And ocular inflammatory disorders are the most common and important extra-articular manifestations with unclear pathogenesis. The imbalance of T help 17 cells (Th17)/regulatory T cells is considered to be a pivotal cause of autoimmune diseases, their roles in spondyloarthropathy, especially the related oculopathy, are rare studied. Objectives: To explore the status of both absolute number and percentage of CD4 +CD25+Foxp3+T regulatory (CD4Treg) cells and Th17 cells in peripheral blood (PB) of patients with spondyloarthropathy-related oculopathy. Methods: Ninety six patients were enrolled, including fifty spondyloarthropathy without related oculopathy (Group A), mean age of 43.23±11.49 years, and fourty six spondyloarthropathy-related oculopathy (Group B), mean age of 43.50±13.51 years. BD Trucount tubes with the lyophilized pellet of a known number of internal counting beads were used for determining absolute counts of total CD4 +T cells in PB and then calculating the absolute number of Th17 cells and CD4Treg. Ninety three healthy volunteers, matched for patients' age and gender, were also included for the estimation of CD4 +T cell subsets. Results: As compared to healthy controls (median of CD4Treg cells: 33.06 cells/ul), the frequencies of circulating CD4Treg cells were significantly decreased in both spondyloarthropathy without related oculopathy (median: 25.07 cells/ul, p<0.05) and spondyloarthropathy-related oculopathy (median: 17.65 cells/ul, p<0.001). The median ratios of Th17/CD4Treg cells in each group of patients were greatly higher than those of healthy volunteers [Group A: 0.29 (0.22, 0.47) vs. 0.21 (0.15, 0.34), p<0.01; Group B: 0.32 (0.21, 0.55) vs. 0.21 (0.15, 0.34), p<0.01]. Nevertheless, there were not significantly different in circulating Th17 cell changes among the three groups. Moreover, there was more absolute reduction of peripheral CD4Treg cells in Group B than Group A (p=0.006), while greater increase in the ratio of Th17/CD4Treg despite no statistical significance (p>0.05). Conclusions: The reduction of CD4Treg but not the elevation of Th17 cells may be the major reason for imbalance of Th17/CD4Treg. It is speculated that spondyloarthropathy-related oculopathy is an autoimmune disease triggered by the defect of immunotolerance. More importantly, the recovery of CD4Treg may be a potential target treatment for patients with spondyloarthropathy-related oculopathy. References: [1] Alunno A, Manetti M, Caterbi S, et al. Altered immunoregulation in rheumatoid arthritis: The role of regulatory t cells and proinflammatory th17 cells and therapeutic implications [J]. Mediators Inflamm2015;2015:751793. [2] Zagora SL, Mccluskey P. Ocular manifestations of seronegative spondyloarthropathies [J]. Curr Opin Ophthalmol2014;25(6):495–501. [3] Khan MA, Haroon M, Rosenbaum JT. Acute anterior uveitis and spondyloarthritis: more than meets the eye [J]. Curr Rheumatol Rep2015;17(9): 59. Acknowledgements: We would like to express our sincere gratitude to all our coworkers and collaborators, to Jing Luo, Xiangcong Zhao, Chen Zhang, Qi Wu, Congcong Liang, and Rui Fu for their technical support. Disclosure of Interest: None declared